Organisational and Pedagocical Conditions of Management of Social Partnership of Sports School with Educational Organisations - Rzhevskaya T. S. (Psychologically Safe Educational Environment: Design Problems and Development Prospects, 2020)
the present research is dedicated to the examination of the peculiarities of educational process in sports school. Organisational and pedagocical conditions of management of social partnership of sports school are analysed in the article.
Keywords: организационно-педагогические условия; социальное партнерство; спортивная школа; social partnership; управление социальным партнерством; organisational and pedagocical conditions; management of social partnership of sports school; sports school